Effect of The Duration of The Diagnosis on DNA Methylation Changes in Three Different Diabetic Genes in Type 2 Diabetes Mellitus - Smail, Harem Othman (Kurdistan Journal of Applied Research, 2024)
The primary epigenetic alteration is DNA methylation. This study examined variations in DNA methylation in patients with type 2 diabetes at various time intervals, concentrating on the Calpain-10 (CAPN10), ATP binding cassette subfamily C member 8 (ABCC8), and Transcription factor 7-like 2 (TCF7L2) genes. Since persistent diabetes can lead to aberrant methylation patterns, it is interested in how long these changes may last. The blood samples from 140 individuals with Type 2 Diabetes Mellitus (T2DM) were collected, and the patients were grouped according to how long they had been diagnosed. Four groups of individuals were created based on their time on the disease: those with T2DM <1 year, those with T2DM 1-3 years, and those with T2DM 3-5 years. The genders and ages of the participants were also noted. Using the Promega technique, bisulfite conversion and DNA extraction were completed. Methylation-specific PCR amplification was used to detect DNA methylation. In the study, ROC curve analysis, Chi-square and Spearman’s correlation coefficients, as well as non-parametric tests, were employed to analyze the methylation percentage variation and methylation patterns among groups. A significant threshold of p < 0.05 was established. The results of the study indicated that the DNA methylation rates of T2DM patients and the control group differed significantly. Patients with type 2 diabetes, particularly those who had just received a diagnosis, showed higher levels of methylation than the control group. The study also found that the length of diagnosis may have an impact on the discriminative strength of the DNA methylation status of the ABCC8 gene, resulting in varying degrees of T2DM prediction.